Perceptions and problems in summary writing: with reference to second year students, faculty of arts, university of jaffna - Thanushan, A. (University of Jaffna, 2022)
Purpose: Among the different genres of writing, summary writing is a complex activity which is very difficult to master. Students encounter many limitations in summary writing. Students usually reproduce the exact sentences from the source text without making any difference. They are unable to separate the main ideas from supporting ideas. The objective of this study is to find out the students' perceptions and problems they encounter in writing summaries. Methodology: The subjects were an intact group of 30 social science students from the Faculty of Arts. Content-Based language instruction was introduced in the second year curriculum. Summary writing was taught as a part of the curriculum. Summary writing activities were implemented in the class over a period of three weeks. The study employed the survey, classroom observation and the interview as methods of data collection. . A semi-structured interview was conducted among students. 25- item-4- point likert scale questionnaires based on student perceptions about summary writing were distributed among students to complete it in the classroom. In the first three weeks, teaching includes types of sentences, transitions, note-taking, paragraph writing, paraphrasing, editing and practices. Summary writing is taught in different approaches. Findings: Although the paragraphs are short, it has long and complex sentences where weaker students could lose their concentration. Those articles are addressed for native speakers so appropriate texts can be simplified for classroom use. The article can be simplified in the form of an adaptation and recreation without changing its discourse. Complexity in teaching summary should be gradually increased. Students find it difficult to separate main ideas from supporting ideas. They perceived that they could improve themselves in writing with more practice. It is the responsibility of the teachers to enhance their note-taking skill from the preliminary level. English classes should provide training in the note-taking and note-reconstruction skills that are required for advanced work in university disciplines. Mostly, the need for contextual learning is emphasized to suit the requirements of learners with diverse backgrounds and priorities. Implications: In the present day classroom, educational needs and approaches are evolving and teachers need to adopt various approaches, methods, pedagogies and approaches to address these evolving needs of students in their learning process. Summary writing is a necessary skill which should be practiced among students in an academic setting. Apart from internal constraints, external constraints such as class size and time constraints should be addressed. Collaborative models of teaching and writing should be introduced in order to foster awareness of this approach. Institutional practices and teachers' training programmes should be facilitated in order to get a successful process writing class.
Keywords: Comprehensive; Perceptions; Performance; Summary writing